Beyond Good and Evil Prelude to a Philosophy of the Future - Nietzsche, Friedrich Wilhelm (Cambridge University, 2013)
Nietzsche's mature masterpiece, Beyond Good and Evil considers the origins and nature of Judeo-Christian morality; the end of philosophical dogmatism and beginning of perspectivism; the questionable virtues of science and scholarship; liberal democracy, nationalism, and women's emancipation. A new translation by Marion Faber, this highly annotated edition is complemented by an introduction by one of the most eminent of Nietzsche scholars, Robert C. Holub. --From publisher's description.